Efficacy and safety of cap-assisted endoscopic mucosal resection for treatment of nonlifting colorectal polyps - Van der Voort, Veronique R. H.; Moons, Leon M. G.; de Graaf, Wilmar; Schrauwen, Ruud W. M.; Hazen, Wouter L.; Seerden, Tom C. J.; Vleggaar, Frank P.; Didden, Paul (Endoscopy, 2021)
Background Suboptimal lifting increases complexity of endoscopic mucosal resection (EMR) for benign colorectal polyps. Cap-assisted EMR (EMR-C) may allow fibrotic polyp tissue to be captured in the snare. This study evaluated the efficacy and safety of EMR-C for benign nonlifting colorectal polyps.Methods This was a multicenter study, which prospectively registered all EMR-C procedures (2016–2018) for presumed benign nonlifting colorectal polyps.Results 70 nonlifting polyps with a median size of 25 mm (interquartile range [IQR] 15–40) were treated with EMR-C. Complete polyp removal was achieved in 68 (97.1 %), including 47 (67.1 %) with EMR-C alone. Overall, 66 polyps showed benign histology, and endoscopic follow-up after a median of 6 months (IQR 6–10) showed recurrence in 19.7 %. First (n = 10) and second (n = 2) benign recurrences were all treated endoscopically. Deep mural injury type III–V occurred in 7.4 % and was treated successfully with clips.Conclusion EMR-C may be an alternative therapeutic option for removal of benign nonlifting polyp tissue. Although recurrence still occurs, repeat endoscopic therapy usually leads to complete polyp clearance.